Psychological incapacity as ground for declaration of marriage nullity an exploratory study - Avelino, Katherine Claudette K.
The topic for this study revolved around Article 36 of the Aquino Family Code. "Psychological Incapacity as Ground for Declaration of Marriage Nullity: an Exploratory Study," Article 36 provides that if a spouse is found to be psychologically incapacitated to perform his or her marital obligations, the marriage shall be declared null and void. However, it can be noted that the term "psychological incapacity" has no specific definition. Therefore the main objective of the study is, according to the range of reasons considered by the judge in the already annulled cases. The researcher studied 100 randomly selected annulled cases from the Regional Trial Courts of Quezon City. Through the case documents, she recorded the petitioners' and respondents' sex, present age, age at marriage. Also included were length of marriage, type of wedding ceremony and number of children. From the case documents, she was able to categorize the reasons considered by the judge to annul the marriage, thereby setting legal parameters to the meaning of psychological incapacity. To reinforce the study, she also conducted informal interviews with some of the judges of the special courts. Results showed the following legal parameters in the use of the term psychological incapacity: vices, wife-battering, womanizing/infidelity, financial matters, abandonment, in-law issues, jealousy, sex/gender-related problems, lack of emotional support, and psychological deviations and disorders. Although these are broader categories, the study also included their specific sub divisions and descriptions. From the results, it seems that much weight is given to the judge's decision, as to whether the respondent is psychologically incapacitated to perform his or her marital obligations. The petitioner has to establish before the court that he or she is no longer satisfied with the marriage relationship because of the incapacity of one of the partners (Veloso, G., 1991, p.2). The following recommendations were drawn up by the student-researcher based on the results of the exploratory study: [For policy implementation] 1.1 A modification of the law should only be made. The filing of annulment should only be allowed by the court if the couple has lived together for at least five years. It is too short a time to judge a spouse to be psychologically incapacitated when one was able live with him or her for only a year or two (In Singapore the minimum number of years of living together before filing a divorce is three years). 2.1 If "psychological incapacity" cannot be identified because it might be too limiting, then an enumeration of examples should be laid out. If a petitioner presented a reason not included in the enumerated examples, the judge sees to it that more or less, it has a semblance with one of the enumeration, or he or she can add the enumerated example according to his or her own judgement. There is often the notion when it comes to annulment, petitions are treated on a case to case basis. The student-researcher is recommending, that clarifications be made providing an enumeration of examples or guiding principles in cases involving Article 36. 3.1 Before the wedding ceremony in church or civil courts: it is highly recommended that a couple be given a compulsory course together with other couples, on Marriage and Family Life. This will not be the typical 2 to 3 days seminar, but a month-long course handled by a professional dealing in this specific field. It is not going to be a passive course, but one that will facilitate interaction among couple, laying down their expectations, needs, fears, etc. 4.1 Before the actual litigation in court, the couple or the petitioner only (when the other partner is not cooperative) should be advised for counseling by a professional therapist. This is just to ensure that every aspect was worked out and looked into before the annulment process. The professional therapist may be a psychologist or a marriage counselor. 5.1 The opinions and the analyses of psychologists and psychiatrists should well be considered during an annulment process, since this is a psychological case. [Academic.] 6.1 Marriage and Family Life courses should be included in the curriculum of high school and college, this time with an in-depth approach. Young people with all their passionate feelings, are prone to thinking that marriage is ecstacy, and that you will be happy because you will spend "eternity" with the person you love ad who loves you in return. Reality should be laid out to them, hat marriage is such a diverse and complex relationship. It is not something that is easy to get out from, just because it's easy to enter into. The stereotype segregation of girls from boys, where girls are made to take up Home Economics and boys, Practical Arts, should be diminished. A family is made up of husband and wife, therefore both sexes are involved in the domestic affairs.